In Vitro Activity of HR 756, a New Cephalosporin, Against Neisseria gonorrhoeae - Murray, Patrick R. (Antimicrob Agents Chemother, 1979)
The in vitro activity of HR 756 was compared with penicillin, cefamandole, cefoxitin, and tetracycline against Neisseria gonorrhoeae. A total of 192 randomly selected isolates (of which 23 had minimal inhibitory concentrations of ≥0.5 μg/ml for penicillin) and three β-lactamase-producing isolates were tested. HR 756 was the most active antibiotic tested, with more than 90% of the isolates inhibited by 0.008 μg/ml and all inhibited by 0.25 μg/ml.